Determinants of Diet Quality Among Pregnant Women Attending Antenatal Care at St. Mary's Mission Hospital, Nairobi County, Kenya - Nyangaresi, Mercy Mosoti (Amref International University, 2024)
Background: Poor diet quality among pregnant women is a significant public health issue, contributing to adverse birth outcomes. Maternal diet is crucial for predicting maternal and child health. Nutrient deficiencies during pregnancy can cause irreversible damage to the fetus, increasing the risks of preterm delivery, low birth weight, impaired child growth, and maternal deaths during delivery. This study assessed the determinants of diet quality among pregnant women seeking antenatal services at St. Mary’s Mission Hospital in Nairobi County. Objectives: The study aimed to determine the quality of the diet, assess maternal characteristics, and establish nutritional literacy among pregnant mothers attending antenatal clinics. The relationships between these variables were also examined. Methodology: The study utilized a descriptive cross-sectional design with consecutive sampling. Data were collected from 248 pregnant women using a questionnaire. Analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The chi-square test was used at the bivariate level and multiple logistic regression at the multivariate level, with a significance level set at P<0.05 Results: The findings indicated that only 9.2% of the participants had good diet quality. Although there was adequate consumption of fruits, vegetables, and legumes, there was poor intake of calcium, iron, omega-3 fatty acids, and folate. Good nutrition literacy was observed in 62.1% of participants. Significant associations were found between diet quality and maternal characteristics, including employment status (AOR=2.845) and receiving health services during ANC visits (AOR=2.937). Fast food consumption was linked to poorer diet quality (AOR=0.821). Nutrition literacy was the strongest determinant of diet quality (AOR=3.79). Conclusion and Recommendation: Pregnant women struggle to meet their nutritional needs, particularly for micronutrients. Employment improves economic status, enabling better diet quality through access to diverse food groups. Nutrition literacy is a significant predictor of meeting maternal nutritional needs. Therefore, enhancing nutrition literacy among pregnant mothers is essential for achieving good diet quality.
Keywords: Pregnant Women, Diet; Nairobi, Kenya